2010
DOI: 10.1007/s13187-010-0156-0
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer Teaching of Medical Students in the UK: Time for a New Approach?

Abstract: Many patients with oral lesions present to general medical practitioners (GMPs). GMPs are also more likely to see patients with higher oral cancer risk. Therefore, GMPs play an important role in the early detection and prevention of oral cancer but is this reflected in undergraduate medical teaching. A questionnaire regarding oral cancer teaching was delivered to the curriculum directors of all UK medical schools. A response rate of 66% was achieved. There was wide variation in teaching time, teaching methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
1
20
1
Order By: Relevance
“…This is analogous to findings of Carter et al [1] and Ogden (2007) [5] who found that oral medicine was the most frequently selected point of referral. Such preference can be explained by the availability of oral medicine specialty at Taibah Dental Hospital which also precludes its generalization to other regions without a dental hospital.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This is analogous to findings of Carter et al [1] and Ogden (2007) [5] who found that oral medicine was the most frequently selected point of referral. Such preference can be explained by the availability of oral medicine specialty at Taibah Dental Hospital which also precludes its generalization to other regions without a dental hospital.…”
Section: Discussionsupporting
confidence: 89%
“…Oral cancer incidence is increasing worldwide in the last decades [1]. 1 Although it is known to be a disease of elderly, younger patients are also affected [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…182,183 The UK study highlighted that undergraduate oral cancer teaching varied widely in terms of duration, format, and content across British medical schools. 184 Its authors recommended the development of a curriculum addressing important aspects of oral cancer from an evidence-based approach that can be integrated into the alreadycrowded undergraduate medical curriculum. 184 There are no data on the awareness, knowledge, and attitudes toward opportunistic oral cancer screening in the Australian GMP population.…”
Section: -173mentioning
confidence: 99%